Markov chain Monte Carlo : innovations and applications - Kendall, W. S.; Liang, F. (Faming), 1970-; Wang, J.-S. (Jian-Sheng), 1960- (Lecture notes series (National University of Singapore. Institute for Mathematical Sciences), 2005)
Markov Chain Monte Carlo (MCMC) originated in statistical physics, but has spilled over into various application areas, leading to a corresponding variety of techniques and methods. That variety stimulates new ideas and developments from many different places, and there is much to be gained from cross-fertilization. This book presents five expository essays by leaders in the field, drawing from perspectives in physics, statistics and genetics, and showing how different aspects of MCMC come to the fore in different contexts. The essays derive from tutorial lectures at an interdisciplinary progr.